FIB-SEM Three-Dimensional Tomography for Characterization of Carbon-Based Materials - Nan Nan; Jingxin Wang (Advances in Materials Science and Engineering)
A review on the recent advances of the three-dimensional (3D) characterization of carbon-based materials was conducted by focused ion beam-scanning electron microscope (FIB-SEM) tomography. Current studies and further potential applications of the FIB-SEM 3D tomography technique for carbon-based materials were discussed. The goal of this paper is to highlight the advances of FIB-SEM 3D reconstruction to reveal the high and accurate resolution of internal structures of carbon-based materials and provide suggestions for the adoption and improvement of the FIB-SEM tomography system for a broad carbon-based research to achieve the best examination performances and enhance the development of innovative carbon-based materials.